Infantile digital fibromatosis. Report of five cases with a review of literature. - Longo, F.; Böhm, P.; Grandi, G.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
5 cases of infantile fibromatosis are reported. The disorder is clinically characterized by fibromatous nodules usually localized on one or more fingers or toes. Histologically, there is a proliferation of myofibroblasts which contain characteristic cytoplasmic inclusion bodies. The relationship with other reactive proliferations which are characteristic of the first months of age and the usefulness of surgical operation are discussed.